Pelestarian Lingkungan dengan Konsep Penghijauan di Desa Kaliburu - Muhammad Alry; Niluh Putu Evvy Rossanty (Lembaga Pengembangan Kinerja Dosen, 2023)
Departing from the problem of disasters that often occur on river banks where when the rainfall is large enough, the river water discharge is also quite dangerous to the surrounding settlements. Therefore, we realized this greening program by planting tree seeds at a number of points around the riverbanks. With the goal of comprehensive river greening, an integrated, comprehensive, sustainable, and insightful plan is needed to think about the environment with the river as a management unit. This community service activity is carried out by the method of (1) community assistance in encouraging increased community participation (2) completion analysis problems and preparation of plans (3) Monitoring and evaluation of work program implementation activities. The main target of this program is community groups and individuals who care highly about the environment with the aim of providing motivation for other communities. With the following stages of implementation: Consultation with the Village, Monitoring Planting Locations, Recruitment of seedlings at the Central Sulawesi Provincial Forestry Service, Planting on the banks of the hamlet 2 river, Planting on the banks of the hamlet 1 river, Planting in the yards of residents' houses, Planting at SD Negeri 2 Sindue Tombusabora, Outreach on the dangers of throwing garbage into rivers and seas, Distributing plant seeds to residents. Greening is a means to overcome the environment so that the environment returns to health free from pollution.